Survivability-Aware Topology Evolution Model with Link and Node Deletion in Wireless Sensor Networks - Yanliang Jin; Xuqin Zhou; Zhishu Bai; Wei Ma; Lina Xu; Zhuo Wu; Su Ki Ooi; Yue Liu (International Journal of Distributed Sensor Networks)
The paper proposes the algorithm of survival topology evolution model. The model applies the survival analysis to the research on the topology of networks. On one hand, it takes the survivability of every node into account. Since the state of a node is affected by the node itself, the environment and so on, it's necessary to study the survivability of nodes. In addition, the survival analysis on the nodes can indicate whether the nodes work well in real time. On the other hand, it also takes the deletion of links and nodes determined by the survivability of the nodes into account. Then it reaches the conclusion by mean field method. The result shows that the degree distributions of WSNs are approximately power law as B-A model and that the survivability of the nodes is proportional to the degree distribution of the network consisting of the previous nodes. These are further confirmed by simulation example.